The Implementation of Local Government Policies in Improving the Quality of Islamic Education in Mandailing Natal District - Siti Hawa Lubis (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
The implementation of policies in Mandaling Natal Regency is that policies are formulated into certain action programs and projects that are designed and financed. The program is implemented according to plan. policy Policies or programs are broadly influenced by the content of the policy and the context of its implementation. The whole policy is evaluated by measuring the level of success of the program based on the policy objectives. Policy is seen through its impact on the intended targets, both individuals and groups as well as society. Government policies, ranging from colonial rule, early and post-independence to the entry of the New Order seemed "irritating", isolated and even almost abolished the Islamic education system because "Indonesia is not an Islamic country".